Integrative RNA-Seq and ATAC-Seq Analysis Reveals the Migration-Associated Genes Involved in Antitumor Effects of Herbal Medicine Feiyanning on Lung Cancer Cells - Wang, Chenyang; Li, Pengxiao; Peng, Yonglin; Liu, Ruiqi; Wu, Xiaoting; Tan, Sheng; Zhang, Ming; Zhao, Xiaodong (Frontiers in Genetics, 2021)
Lung cancer is one of leading cause of cancer-associated death in the world. It is of great importance to explore new therapeutic targets. Traditional Chinese medicine formula Feiyanning has been clinically administered in China for more than a decade and raised an attention due to its anti-cancer effect in lung cancer. However, the underlying molecular mechanisms remains to be elucidated. In the present study, we carried out cellular and molecular assays to examine the anti-tumor activities and to understand the mechanism of Feiyanning formula in lung cancer cells. The cells viability assay was performed by the Cell Counting Kit-8. Wound healing assay was carried out to examine the cellular migration ability. The effect of Feiyanning formula on invasion of lung cancer cells was examined by Trans-well assay. Transcriptome and chromatin accessibility analysis by RNA-seq and ATAC-seq was performed to investigate the underlying molecular mechanisms. Our results revealed that Feiyanning formula inhibited the cellular activities of proliferation, migration and invasion in non-small cell lung cancer cell lines A549, H1975 and 95D. Furthermore, we observed that the transcriptional activity of the migration-associated genes was down-regulated upon Feiyanning formula treatment in non-small cell lung cancer cells. The chromatin accessibility of Feiyanning-treated lung cancer genome tended to decrease, in which the regulation of cellular component movement biological process and PI3K-AKT pathway were enriched. Taken together, the present study suggested that Feiyanning formula exerted the anti-tumor effects by modulating the expression and chromatin accessibility levels of migration-associated genes.